La pedagogía de Waldorf para fortalecer la lectoescritura en el séptimo grado de Educación General Básica - González Ramón, Dania Michelle (2024)
The present research titled: Waldorf Pedagogy to strengthen reading and writing in the seventh grade of Basic General Education, had as general objective: Determine the incidence of Waldorf pedagogy in strengthening reading and writing in the seventh grade of Basic General Education of the “San José de Calasanz” Educational Unit, Saraguro, 2023-2024, this general objective was supported by three specific objectives that focused on: Diagnosing literacy in the seventh year of Basic General Education, also, Planning a proposal to strengthen literacy in the seventh grade of Basic General Education using Waldorf pedagogy and Evaluate the incidence of Waldorf pedagogy in strengthening literacy; This research was descriptive with a mixed approach and non-experimental design. In addition, methods such as: scientific, statistical, analytical, synthetic and descriptive were used; Techniques were used such as: the interview directed at the teacher and the Magellan Scale test for reading and writing, the population that was considered for the execution of this project were the seventh grade students of the Fiscomisional Educational Unit “San José de Calasanz” who were selected through non- probabilistic sampling, which was based on the type of convenience sample. The application of Waldorf pedagogy has proven to be effective and has provided satisfactory results in strengthening the teaching and learning process of literacy, through a gradual, artistic, narrative approach, and focused on the individuality of the student, promoting a comprehensive development of children through enriching experiences that support their educational and human development.